2002
DOI: 10.1097/00000539-200201000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Doses of a Commercially Prepared Oral Midazolam Syrup in Children

Abstract: Commercially prepared oral midazolam syrup is effective in producing sedation and anxiolysis in doses as small as 0.25 mg/kg; there is a slightly faster onset with increasing the dose to 1.0 mg/kg. At all doses, 97% of patients demonstrated satisfactory sedation, whereas 86% demonstrated satisfactory anxiolysis when the face mask was applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 31 publications
3
79
1
Order By: Relevance
“…The commercial preparations come in a variety of flavors that are highly accepted by children. Oral midazolam syrup is effective for producing sedation and anxiolysis within 10 to 20 min at such low doses as 0.25 mg/kg (Coté et al, 2002). Furthermore, midazolam has minimal effects on respiration and oxygen saturation even when administered at doses as large as 1.0 mg/kg (maximum, 20 mg) as the sole sedating medication to healthy children in a supervised clinical setting.…”
Section: Gabaergic Inhibition In Anesthesiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The commercial preparations come in a variety of flavors that are highly accepted by children. Oral midazolam syrup is effective for producing sedation and anxiolysis within 10 to 20 min at such low doses as 0.25 mg/kg (Coté et al, 2002). Furthermore, midazolam has minimal effects on respiration and oxygen saturation even when administered at doses as large as 1.0 mg/kg (maximum, 20 mg) as the sole sedating medication to healthy children in a supervised clinical setting.…”
Section: Gabaergic Inhibition In Anesthesiologymentioning
confidence: 99%
“…Although there is a statistically significant relationship between the dose and time of onset for both sedation and anxiolysis, this difference is probably not clinically important. Satisfactory sedation and anxiolysis seem to last for up to 40 to 45 min (Coté et al, 2002). In comparative studies, parents of children undergoing bone marrow biopsy preferred midazolam to fentanyl for sedation (Sandler et al, 1992).…”
Section: Gabaergic Inhibition In Anesthesiologymentioning
confidence: 99%
“…before the procedure. 10 Patients were wheeled into the operation theatre, Standard Monitors like Pulse Oximeter, Blood pressure, ECG were connected and after recording Baseline parameters IV line accessed via 22G or 24G IV cannula, Ringer lactate maintenance fluid started, 11 the child was preoxygenated with 100% O2 for 3 minutes and induced with Inj. fentanyl 2 mic/kg IV and Inj.…”
Section: Study Methodsmentioning
confidence: 99%
“…The beneficial effects of midazolam include sedation, anxiolysis, and reduction of postoperative vomiting. A recent evidence-based clinical update has shown that oral midazolam (5) 0.5 mg/kg is effective in reducing both separation and induction anxiety in children, with minimal effect on recovery time. However, the acceptability of oral midazolam by pediatric patients is only 70%.…”
Section: Introductionmentioning
confidence: 99%